Effects of Scutellaria baicalensis, Folium Artemisiae argyi, and Galla Chinensis on the protein expression and resistance genes of Exiguobacterium sp. in response to gentamicin - Xiaohui Wang; Chang Luo; Hua Zhang; Jian Huang; Lei Sun; Tao Ma (Scientific Reports)
Abstract Currently, the issue of antibiotic resistance genes as emerging pollutants in the environment has attracted significant attention in the field of environmental pollution research. Moreover, plant-derived compounds has become a research hotspot due to its high efficiency and low toxicity in reversing microbial intracellular antibiotic resistance genes. However, there is little research on the impact of specific plant extracts on proteins and antibiotic resistance genes during the process of reversing antibiotic resistance genes. In this study, the phosphorus removal performance test, combined with protein Raman spectroscopy analysis and antibiotic resistance gene abundance detection methods, was employed to investigate the effects of Scutellaria baicalensis, Folium Artemisiae argyi, and Galla Chinensis on the phosphorus removal rate, intracellular protein binding sites, and antibiotic resistance gene abundance of Exiguobacterium sp. after exposure to gentamicin. The Raman spectroscopy test results revealed a shift in the protein peaks of Exiguobacterium sp., transitioning from the stable C = C = C = C, C = C, C = C = C structures found in drug-resistant Exiguobacterium sp. to unsaturated bonds of C, CH2, olefinic unsaturation, and H bonds, similar to those of normal Exiguobacterium sp. Furthermore, the antibiotic resistance gene abundance test results indicated a significant reduction in the abundance of gentamicin resistance genes within the intracellular environment of Exiguobacterium sp. following treatment with these plant extracts. The potential roles of flavonoids in Scutellaria baicalensis and Folium Artemisiae argyi, and tannins in Galla Chinensis in reversing resistance were discussed.